Identifikasi Tujuan Tata Kelola Teknologi Informasi PLT FST UIN Jakarta Menggunakan Framework COBIT 2019 - Aeni Hidayah, Nur; Nurbojatmiko; Ade Arfani, Mizan; Yuliwanda Anggi Kusumaatuti (Journal of Applied Computer Science and Technology, 2024)
Information technology (IT) has an important role in increasing efficiency and providing benefits to decision making in various sectors. IT governance is important for organizational sustainability and performance. This research focuses on the Integrated Laboratory Center (PLT) FST UIN Jakarta which still depends on external parties for IT governance, creating potential risks and uncertainty in its operations. Therefore, this research aims to analyze the implementation of COBIT 2019 as a guide in identifying IT governance objectives that suit the needs of PLT FST UIN Jakarta. The research method used in this research involves the COBIT 2019 theoretical approach, with a focus on the goal cascade concept. This approach enables a systematic translation process of stakeholders' needs for IT systems into more specific goals and appropriate strategic steps. The results show eight COBIT 2019 domains that are relevant to IT governance objectives in PLT, which include APO02 (Managed strategy), APO08 (Managed relationships), APO10 (Managed vendors), APO11 (Managed quality), BAI04 (Managed availability and capacity), DSS01 (Managed operations), DSS03 (Managed problems(, and MEA02 (Managed system of internal control) The recommendations resulting from this research are designed to improve the performance and maturity of IT processes at PLT FST UIN Jakarta in accordance with the IT governance objectives that have been identified. This is expected to provide a stronger foundation for managing and optimizing the use of IT to support operations and achieve organizational goals more effectively.